2016
DOI: 10.1007/s12032-016-0754-8
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and cyclin E2 are differentially expressed in gastric cancer

Abstract: Cell cycle regulators cyclin D1 and cyclin E2 function in G1/S transition by activating downstream cyclin-dependent kinases. Deregulated expression of these cyclins has been reported in various cancers. However, little is known about their clinical significance in gastric carcinoma. We aimed to explore that whether there is differential expression of these cyclins in clinically distinct gastric cancer patients. In this study we recruited a total of 92 subjects including 20 controls and 72 cases of histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…CCND1, which is required for progression through the G1 phase of the cell cycle, is rapidly synthesized during that phase and then degraded during S phase. CCND1 also dimerizes with cyclin-dependent kinases (CDK) 4/6 to regulate the G1-S phase transition and inhibits retinoblastoma protein (pRb) activity, and overexpression of CCND1 is associated with tumor progression in gastric and other cancers [31, 32]. Surprisingly, we found that UBE2T knockdown resulted in cell cycle arrest at the G2/M phase rather than the G1/S phase.…”
Section: Discussionmentioning
confidence: 86%
“…CCND1, which is required for progression through the G1 phase of the cell cycle, is rapidly synthesized during that phase and then degraded during S phase. CCND1 also dimerizes with cyclin-dependent kinases (CDK) 4/6 to regulate the G1-S phase transition and inhibits retinoblastoma protein (pRb) activity, and overexpression of CCND1 is associated with tumor progression in gastric and other cancers [31, 32]. Surprisingly, we found that UBE2T knockdown resulted in cell cycle arrest at the G2/M phase rather than the G1/S phase.…”
Section: Discussionmentioning
confidence: 86%
“…A growing number of studies have detected the abnormally activated Wnt signaling during tumor process [30,31]. The protein encoded by CCND1 belongs to the highly conserved cyclin family, and its members have a signi cant periodicity of protein abundance throughout the cell cycle progression [32]. CCND1 variation is frequently observed during tumor process [33].…”
Section: Discussionmentioning
confidence: 99%
“…The CCND1 gene, located on chromosome 11q13, is a well-known oncogene that is frequently overexpressed in various kinds of human cancers, such as breast cancer (34), lung cancer (35), gastric cancer (36) and bladder cancer (37). In pancreatic cancer, CCND1 was overexpressed in tumour tissues; the expression of this gene is significantly correlated with extent of differentiation and poor prognosis (38,39).…”
Section: Discussionmentioning
confidence: 99%